PEMANFAATAN TANAH SEKITAR SEBAGAI MATERIAL INTERLOCK BLOCK - akram bikram (Jurnal Proyek Teknik Sipil, 2020)
Soil characteristics around Kendari City are included in the clay soil category. So far, clay has not been used optimally. Clay is only used as pile material in buildings. Land around the city of Kendari can be made of brick interlock material. This research is important to be carried out to utilize the surrounding land as building wall material, to obtain an economical and effective wall material.This study aimed to test the quality of interlock brick material from the surrounding soil in Kendari City. In this study three treatments were made. Each treatment made 10 test specimens. Test specimens are made with a size of 25 cm x 12.5 cm x 10 cm. The steps of conducting research are the preparation of work tools, preparation of work materials, dry stirring process, moist stirring process, printing, drying, watering, testing, and data analysis. Data collection techniques carried out in the laboratory. Testing includes compressive strength and water absorption. Based on the results of tests in the laboratory that interlock block material from surrounding soil is suitable for use as building wall material in a simple house on condition that the quality of the concrete frame structure is improved.